Performance of three meat type chicken farms maintained at different bio-security levels - Hannan, MA; Ahmed, MB; Islam, SS (Bangladesh Journal of Animal Science, 2020)
Because of the high density of the poultry flocks in current commercial production operations and the inherent disease risks associated with this type of production, proper bio-security practices are very important for successful poultry farming. The study was undertaken to investigate the productive and economic performances of poultry farms keeping three different meat types chickens under good, fair and poor bio-security conditions in south western regions of Bangladesh. The three meat type chickens under consideration were Cobb 500 broiler strain, cockerel and Sonali (RIR x Fayoumi crossbred). According to obtained marks each of one hundred (total three hundred) surveyed farms were divided into good (≥ 80%), fair (61-79%) and poor (≤ 60%) bio-secured categories. Results revealed that market body weight, total feed intake, efficiency of feed utilization, survivability, gross return and net return of Cobb 500 broiler, cockerel and Sonali farms showed higher trends from poor to good bio-secured farms. The survivability was significantly (p<0.01) higher under good than that of fair and poor bio-secured level. The highest survivability was observed in farms kept Sonali followed by cockerel and Cobb 500. The result revealed that the Sonali was the highly benefited chicken farms than Cobb 500 broiler strain and cockerel. The broiler farms were more bio-security sensitive than Sonali and cockerel farms. Hence, good bio-security practices had significant impact on productive and economic performances of all three categories of meat type chickens. It can be concluded that the meat type chickens are more sensitive to the bio-security measures of the farms and Sonali farms are more beneficial from economic point of view as compared to cockerel and Cobb 500 farms. Bang. J. Anim. Sci. 2020. 49 (1): 63-70